Hypertensive Crisis - Romi Ermawan; Andi Annisa Amaliah Darman; Nimas Resti; Putu Diva Gayatri Jaya Putri; Yusuf Alfin Firmawan; Siti Jaisy Millah Hadaina (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2023)
Hypertension in global burden disease and is expected to increase by 29% in 2025. one of the emergency condition that can arise from hypertension is hypertensive crisis. Hypertensive crisis is an increase of systolic blood pressure >179 mmHg and diastolic blood pressure > 109 mmHg. By the present of target organ damage, hypertensive crisis is classified as hypertensive urgency and hypertensive emergency.Hypertensive crisis occurs based on several mechanisms, failure of the autoregulation system, activation of renin-angiotensin-aldosterone system, and prothrombotic state. This mechanisms cause ischemia and induces a hypertensive crisis. Management of hypertensive crisis is to restore systolic blood pressure in range 100-110 mmHg. In hypertensive emergency case, blood pressure should be reduced slowly to 20-25% in first hour and 160/100 mmHg in the next 2 to 6 hours, except in hypertensive emergency case that cause aortic dissection. Therapy of hypertensive crisis including arterial and venous vasodilators, ACE inhibitor, calcium antagonists, and diuretics.